Effect of different fermentation strategies on Bacillus thuringiensis cultivation and its toxicity towards the bagworm, Metisa plana Walker (Lepidoptera: Psychidae) - Mohd Masri, Mohamed Mazmira; Ariff, Arbakariya (Egyptian Society for Biological Control of Pests, 2020)
The effect of batch and fed-batch fermentation on the cultivation performance of Bacillus thuringiensis was investigated using a 5-l stirred tank bioreactor. Significantly higher viable cell count (> 1.5 × 1012 CFU/ml) was obtained in the fed-batch compared to batch fermentation (1.4 × 1012 CFU/ml). Glucose feeding during the fermentation seemed to enhance cell growth but failed to enhance the sporulation rate. It was found that sporulation and δ-endotoxin synthesis in fed-batch fermentation could be enhanced by the application of optimal dissolved oxygen tension (DOT) control strategy without affecting the cell growth. Fed-batch cultivation with feeding at the exponential growth phase where the DOT was switched from 80 to 40% at 12 h of cultivation recorded the highest spore count of 7.1 × 1011 spore/ml. Cultures obtained from batch cultivation, as well as fed-batch cultivation with feeding at lag or exponential growth phase and the application of optimal DOT control strategy, recorded the presence of δ-endotoxin; however, none was detected in intermittent fed-batch fermentation. Bioassay data against the bagworm Metisa plana Walker (Lepidoptera: Psychidae) recorded the highest corrected mortality (80%) at 7 days of treatment (DAT), using the culture obtained from fed-batch cultivation with feeding during the exponential growth phase, and the DOT was switched from 80 to 40% at 12 h of cultivation. It is important to note that all cultures containing δ-endotoxin exhibited 100% mortality towards M. plana at 14 DAT.